Rock Slopes Stability Analysis Of AL-Nfayil Formation at Bahr Al-Najaf Basin -middle of Iraq:case study - Jaffar H.A. Al-Zubaydi (Al-Qadisiyah Journal of Pure Science, 2018)
Field  studies of  the (Subhorizontal-layer) slopes of  AL-Nfayil formation, middle  of Iraq, revealed the abundance of rock slope failures, the dominant types are rock fall, Secondary toppling, and rolling. Slope stability assessment was carried out by stereographic projection. Secondary Toppling  mechanisms (generally due to the effects of differential weathering and or Erosion, undercutting as well as the discontinuities surrounding the rock mass ) include mechanism. Some measures are proposed to stabilize the slopes including removal of blocks liable to toppling in the critical cases, and  con struction of retaining wall .